National trends in loneliness and social isolation in older adults: an examination of subgroup trends over three decades in Sweden - Dahlberg, Lena; von Saenger, Isabelle; Naseer, Mahwish; Lennartsson, Carin; Agahi, Neda (Frontiers in Public Health, 2024)
Introduction Loneliness and social isolation are public health concerns. This study aimed to examine levels and trends in loneliness and social isolation among older adults (77+ years) in Sweden, assess subgroup variations, and determine associations between loneliness and social isolation. Methods The 1992, 2002, 2004, 2011, 2014 and 2021 waves of the Swedish Panel Study of Living Conditions of the Oldest Old (SWEOLD) were analysed through ordered logistic and linear regressions. Results On average, 12.5 percent of the participants experienced loneliness often/nearly always, while 6 percent were categorised as severely isolated. Loneliness and social isolation were more common in women, those aged 85+, and persons with basic education, in psychological distress or with mobility limitations. Loneliness was also associated with living alone. No increases in loneliness or isolation were identified; instead, loneliness tended to decrease in groups already experiencing lower levels of loneliness. Loneliness and social isolation were moderately associated each survey year. Discussion This study challenges perceptions of high and increasing levels of loneliness and social isolation. Given the impact on health and wellbeing and the ageing of populations, policy and practice should still address these issues and target vulnerable groups. Subgroup analyses in trends are scarce and should be explored further in future research.